2013
DOI: 10.3961/jpmph.2013.46.6.353
|View full text |Cite
|
Sign up to set email alerts
|

A Trend Analysis of the Prevalence, Awareness, Treatment, and Control of Hypertension by Age Group

Abstract: ObjectivesWe examined the trends in prevalence, awareness, treatment, and control of hypertension in Korea as a basis for improving hypertension control programs.Methods12 598 participants of the Korean National Health and Nutrition Examination Survey were included in this study. Weighted linear regression to test time trends from 2007 to 2011 was performed.ResultsThe prevalence of hypertension was 20.7% in 2007, 29.4% in 2009, and 26.2% in 2011. Awareness of hypertension was 64.8% in 2007 and 61.1% in 2011. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…We found that gender is associated with hypertension awareness and treatment; men had larger hypertension prevalence than women among young and middle-aged hypertensive patients but had a lower incidence of awareness and treatment of hypertension than women. This result is similar to those reported in a study in north China 31 , a study in Korea 32 and a study in Malaysian 33 . There are some researchers in China who concluded that the rates of awareness, treatment and control of hypertension in women were higher than that in men 14 , 34 , 35 .…”
Section: Discussionsupporting
confidence: 92%
“…We found that gender is associated with hypertension awareness and treatment; men had larger hypertension prevalence than women among young and middle-aged hypertensive patients but had a lower incidence of awareness and treatment of hypertension than women. This result is similar to those reported in a study in north China 31 , a study in Korea 32 and a study in Malaysian 33 . There are some researchers in China who concluded that the rates of awareness, treatment and control of hypertension in women were higher than that in men 14 , 34 , 35 .…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified several non‐modifiable factors for the worse management of hypertension, such as male gender and younger age. These observations are in keeping with the results of numerous previous studies 19,20 . We might have to build technological platforms to tackle the problems in these special populations.…”
Section: Discussionsupporting
confidence: 87%
“…Systolic and diastolic BPs were measured 3 times, and the average of the second and third measurements was used for analysis (9,10 (11,12). The National Health Examination followed a standard procedure, the details of which were published previously (9).…”
mentioning
confidence: 99%